SIKAP MASYARAKAT TERHADAP PRODUK DETERJEN DI KOTA YOGYAKARTA - Wendri Rusli (Jurnal Riset Manajemen dan Bisnis, 2011)
This study examines the effect ofadvertisement, brand, dan product quality on society attitudein Yogyakarta. Thesampleis drawn with a stratified random precedure, resulted on therespondents 100 fromyogyakarta society. Using Ajzen and Fishbein analysis, the results showthat advertisement, brand, and product qualityinfluence on society’s attitude in Yogyakarta.Keywords: Advertisement, Brand, Product Quality, Attitude